Diagnostic Performance of Shear Wave Elastography for Predicting Esophageal Varices in Patients With Compensated Liver Cirrhosis. (20th May 2016) - Kim, Tae Yoon; Kim, Tae Yeob; Kim, Yongsoo; Lim, Sanghyeok; Jeong, Woo Kyoung; Sohn, Joo Hyun
Abstract : Objectives: The purpose of this study was to investigate the diagnostic performance of shear wave elastography (SWE) for predicting the presence of esophageal varices and high‐risk esophageal varices in patients with compensated cirrhosis and to compare it with other nonspecific predictors and according to the presence of splenomegaly. Methods: Clinical data from 103 patients with compensated cirrhosis who underwent sonography, SWE, and endoscopy were collected consecutively. Liver stiffness was measured by SWE. Comparisons of the accuracy of prediction between groups were made by areas under the receiver operating characteristic curves (AUROCs), and regression analyses were performed for the multiple variables related to the presence of esophageal varices and high‐risk varices. Results: The optimal cutoff values for predicting the presence of esophageal varices and high‐risk varices were 13.9 and 16.1 kPa, respectively. The AUROC of liver stiffness for prediction of esophageal varices was significantly higher than the AUROCs of platelet count, spleen diameter, and platelet count/spleen diameter ratio ( P = .025; P = .001; P = .027). For predicting esophageal varices in patients without splenomegaly, the AUROC of liver stiffness was higher than that of the platelet count/spleen diameter ratio. In multivariate logistic regression analysis, liver stiffness and the platelet count/spleen diameter ratio were independent predictors of esophageal varices ( P < .001; P = .038). For the presence of high‐risk varices, only liver stiffness was a statistically significant independent predictor ( P = .012). Conclusions: In patients with compensated cirrhosis, liver stiffness measured by SWE is a new effective noninvasive diagnostic tool for predicting the presence of esophageal varices. It is more accurate than the platelet count/spleen diameter ratio, especially in patients without splenomegaly. In addition, the SWE value was the only effective independent factor for predicting high‐risk esophageal varices.